INTERVENSI HUKUM ISLAM TERHADAP HUKUM KEWARISAN ADAT MINANGKABAU - Marlina, Selfia; Yenti, Endri (El-Ahli : Jurnal Hukum Keluarga Islam, 2023)
Abstract Minangkabau has two forms of inheritance, namely high inheritance and low inheritance and the kinship system in Minangkabau adheres to the matrilineal principle. Because in Minangkabau custom there are two forms of inheritance distribution, namely individual and collective, so there are differences in inheritance distribution in adat and Islamic law. The Compilation of Islamic Law which is a collection of rules used as a reference for Muslims in Indonesia also regulates inheritance. This study aims to see whether Islamic law intervenes in customary law, especially in the Compilation of Islamic Law regarding inheritance. This study uses a literature review (library research) with a descriptive method through a qualitative approach with the main data coming from journals, books, and the internet. Data collection is done by reading, taking notes and comparing according to the themes discussed. The results of this study indicate that there is an intervention Islamic law regarding the inheritance system that exists in Minangkabau custom in several articles in the Compilation of Islamic Law, for low inheritance in its distribution in customary law and KHI both use faraidh law, while high inheritance according to KHI is not included in inheritance because ownership cannot be individually owned. Keyword: Islamic Law, Minagkabau Inheritance